WORD MEANING AND ITS MEASURING TOOLS - Nino Kemertelidze; Tamar Manjavidze (European Scientific Journal, ESJ, 2014)
A certain thing or phenomenon has its name in a certain language, i.e. has a definite meaning. In another language the same thing or phenomenon is expressed otherwise. A word meaning can be changed as many times as the author wants to use it in different contexts. It is namely a context where a word constantly acquires new meanings. In order to properly understand any utterance one should understand not only words and word combinations but also deeply comprehend what stands behind them, what they indicate to. Namely this is the so called new meaning that is subjective at a certain degree. This meaning can also be changed according to the association a thing (phenomenon) arouses in people, what emotions and feelings it provokes in them. It will be incorrect to prove that this word should be evaluated positively, and that one – negatively as one and the same notion can be positive for a certain person, negative – for another and even neutral for someone else. Consequently, the following issue becomes interesting: does evaluation come from perception or perception – from evaluation? We consider that both of these processes are interrelated and interwoven.